Conjugate addition to (alpha,beta)(alpha ',beta ')-diendioate esters by lithium (alpha-methylbenzyl)benzylamide: tandem addition-cyclisation versus double addition - Urones, J; Garrido, N; Diez, D; Dominguez, S; Davies, S (1999)
Strategies for obtaining either the products from tandem conjugate addition-cyclisation or from double addition in the highly stereoselective addition of lithium (R)-(β-methylbenzyl)benzylamide to (α,β)(α,β)- diendioate esters are demonstrated.